Reconceptualizing Smart Tourism Governance Beyond the City: A Bibliometric Analysis of Rural and Ecological Perspectives - Andi Yulianto; Roby Setiadi; Miswanto Miswanto; Muhammad Iqbal Al-Banna Ismail (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study maps the knowledge structure and thematic evolution of smart and rural tourism research, focusing on governance’s role in sustainability-oriented rural contexts. This addresses the conceptual imbalance in the literature, which remains largely urban-centric and technology-driven. Research Methodology: A bibliometric analysis was conducted on 114 articles indexed in the Scopus database using VOSviewer, including keyword co-occurrence, thematic clustering, and overlay visualization to identify major themes and research trends. Results: The findings indicate a rapid growth in smart tourism research; however, the literature is still dominated by technology-oriented and smart city perspectives. Seven thematic clusters were identified, revealing a fragmented knowledge structure in which rural, ecological, and community-based tourism remain peripheral to the core. Although governance and sustainability have gained increasing attention, their integration with core smart tourism concepts remains limited. Conclusions: This study proposes a rural-ecological governance perspective that positions governance as a mediating mechanism linking digital transformation, community participation, and ecological sustainability in rural tourism. Limitations: The analysis was limited to Scopus-indexed publications and did not incorporate empirical field-based evidence. Contributions: This study clarifies the intellectual structure of smart tourism research and offers a conceptual direction for future research and policy development in sustainable smart tourism.